1991
DOI: 10.1182/blood.v78.10.2520.2520
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of two different doses of cytarabine for acute myeloid leukemia: a phase III trial of Cancer and Leukemia Group B

Abstract: Between 1982 and 1986, 326 evaluable patients with acute myeloid leukemia (AML) were randomized to receive cytarabine (Ara-C) at 200 mg/m2 (A200) or 100 mg/m2 (A100) for induction and maintenance therapy. Cycle 1 of induction therapy consisted of 7 days of continuous intravenous (IV) Ara-C and 3 days of i.v. daunorubicin (DNR); cycle 2, if needed, consisted of 5 days of Ara-C and 2 days of DNR. Complete responders (CR) then received monthly subcutaneous (SC) Ara-C at the respective doses (A100 or A200) with 6-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(28 citation statements)
references
References 16 publications
1
25
0
1
Order By: Relevance
“…However, overall the protocol provided long-term survival seemingly superior to other studies in elderly AML patients. One-third of our patients survived 2-3 years, whereas this figure typically is <20% (Dillman et al, 1991;Mayer et al, 1994;Lowenberg et al, 1997;Amadori et al, 2001;Goldstone et al, 2001;Stone et al, 2001;Anderson et al, 2002;Baer et al, 2002) in studies with a high degree of patient selection, as well as for our non-protocol patients. A major prerequisite for our positive study result is likely to be the low early death rate of 11% (intention-to-treat analysis), in comparison with 20-54% in several published studies (Mayer et al, 1994;Hiddemann et al, 1999;Goldstone et al, 2001;Anderson et al, 2002;Baer et al, 2002;Wrzesien-Kus et al, 2002).…”
Section: Discussionmentioning
confidence: 73%
“…However, overall the protocol provided long-term survival seemingly superior to other studies in elderly AML patients. One-third of our patients survived 2-3 years, whereas this figure typically is <20% (Dillman et al, 1991;Mayer et al, 1994;Lowenberg et al, 1997;Amadori et al, 2001;Goldstone et al, 2001;Stone et al, 2001;Anderson et al, 2002;Baer et al, 2002) in studies with a high degree of patient selection, as well as for our non-protocol patients. A major prerequisite for our positive study result is likely to be the low early death rate of 11% (intention-to-treat analysis), in comparison with 20-54% in several published studies (Mayer et al, 1994;Hiddemann et al, 1999;Goldstone et al, 2001;Anderson et al, 2002;Baer et al, 2002;Wrzesien-Kus et al, 2002).…”
Section: Discussionmentioning
confidence: 73%
“…It has been suggested that neutropenia after chemotherapy lasts longer in older patients (15) and that a defective pool of hematopoietic stem cells could prolong myelosuppression (16). The age‐related differences in the disease biology explain in part why patients 60 years of age and older do not achieve the same remission rates (17–27) and remission duration (20, 23, 25–27) as younger patients. On the other hand, inadequate antileukemic treatment might also have contributed to the inferior results as chemotherapy intensity has commonly been reduced in older patients.…”
Section: Acute Myeloid Leukemia In Older Patients As a Challengementioning
confidence: 99%
“…The age‐related study results are listed in Table 1 in the order of increasing age in the groups of patients treated (16–27, 30–40, 43–48). If age specific therapeutic results were reported, the related publications were listed for separate age groups.…”
Section: Age and Trends In Chemotherapymentioning
confidence: 99%
“…Results using an anthracycline combined with a 7 d c.i.v. infusion of either 100 or 200 mg/m 2 daily of Ara‐C are comparable (Dillman et al , 1991). Extending the Ara‐C infusion to 10 d showed no advantage over 7 d (Preisler et al , 1987).…”
Section: Induction Chemotherapymentioning
confidence: 99%